Is there a correlation between inflammatory markers and coagulation parameters in women with advanced ovarian endometriosis? - Shaojie Ding; Qiao Lin; Tianhong Zhu; Tiantian Li; Libo Zhu; Jianzhang Wang; Xinmei Zhang (BMC, 2019)
Abstract Background Endometriosis is defined as a chronic inflammatory disease. Recent studies have shown that increased coagulation parameters including fibrinogen and platelets are associated with endometriosis. The objective of this study was to determine the levels of inflammatory markers and coagulation parameters and their correlations in women with endometriomas compared to those with benign ovarian cysts or normal pelvic anatomy. Methods Between June 2015 and June 2017, a total of 548 women who underwent laparoscopic/laparotomic surgery for ovarian endometriomas (OMA group, n = 226), non-endometriosis benign ovarian cysts (Cyst group, n = 210) and tubal reanastomosis (Control group, n = 112) were recruited in this study. Inflammatory markers including c-reactive protein (CRP), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR) and coagulation parameters including platelet count, thrombin time (TT), prothrombin time (PT), activated partial thromboplastin time, and plasma fibrinogen as well as CA-125 were determined. Results Compared with Cyst group and Control group, TT and PT in OMA group were significantly shorter and plasma fibrinogen levels were significantly higher (P < 0.05). Moreover, the levels of plasma fibrinogen were positively correlated with CRP, NLR and PLR (P < 0.05). In addition, the confidence intervals for the area under the curve (AUC) for CA-125 × fibrinogen were significantly higher than those for CA-125 (0.904-0.952 vs. 0.899-0.949) in the diagnosis of endometrioma. Conclusions These results indicate that women with endometriomas demonstrate a hypercoagulable status due to the inflammatory nature of endometriosis. The combined determination for CA-125 and fibrinogen demonstrate a higher area under the curve than the single detection of CA-125 in those with endometriomas compared to these with benign ovarian cysts. Trial registration This study was approved by the Human Ethics Committee of the Women's Hospital, School of Medicine, Zhejiang University (No.20170174) and all women provided written informed consent.